1978
DOI: 10.1007/bf01219423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenformin on hepatic balances of gluconeogenic substrates in man

Abstract: Summary. The effect of a five day pretreatment with phenformin (3 • 50 mg daily) on hepatic metabolism was studied in six healthy volunteers. Arterial and hepatic venous concentrations of substrates and hepatic blood flow were estimated during a basal period and during a low-dose lactate infusion (0,03 mmol 9 kg -~ 9 min-1). The results have been compared with those obtained from untreated normal subjects in a previous study (16). During the baseline period arterial concentration of alanine and the hepatic ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Dietze and his colleagues 70 have for the first time clearly showed in man receiving phenformin in therapeutic doses that net splanchnic clearance of lactate and production of glucose are re-LACTIC ACIDOSIS REVISITED duced during lactate infusion (up to blood lactate concentrations of 1.74 mmol/L). The work of Arieff and his colleagues 17 in dogs showed that extrahepatic splanchnic lactate production was increased and hepatic uptake reduced in the presence of phenformin.…”
Section: Newer Clinical and Pathophysiologic Aspects Of Lactic Acidosismentioning
confidence: 97%
“…Dietze and his colleagues 70 have for the first time clearly showed in man receiving phenformin in therapeutic doses that net splanchnic clearance of lactate and production of glucose are re-LACTIC ACIDOSIS REVISITED duced during lactate infusion (up to blood lactate concentrations of 1.74 mmol/L). The work of Arieff and his colleagues 17 in dogs showed that extrahepatic splanchnic lactate production was increased and hepatic uptake reduced in the presence of phenformin.…”
Section: Newer Clinical and Pathophysiologic Aspects Of Lactic Acidosismentioning
confidence: 97%